ATTENUATING SCOLLOSIS BY ADAPTING JUDO-SPECIFIC MEANS - A. NEOFIT; M. ION-ENE (Editura Universitatii Transilvania din Brasov, 2018)
The study aims at assessing the extenuative anthropometric and functional improvements of scoliosis in children as a result of a kinetotherapeutical program with exercises adapted from judo. The study included 18 aged 10-14 years, diagnosed with levoconvex thoraco-lumbar scoliosis. The kinetotherapeutical program adapted from judo was applied for 3 months. The results of the study highlight significant differences in the anthropometric and somatic parameters contributing to improving the spine condition. The efficiency of kinetotherapeutical programs depends on the early start of treatment and the effectiveness of specific physical exercise programs.